2020
DOI: 10.1111/jvp.12898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose on the intravenous pharmacokinetics of tolfenamic acid in goats

Abstract: The objective of this study was to determine the pharmacokinetics of tolfenamic acid (TA) following intravenous (IV) administration at doses of 2 and 4 mg/kg in goats. In this study, six healthy goats were used. TA was administered intravenously to each goat at 2 and 4 mg/kg doses in a cross‐over pharmacokinetic design with a 15‐day washout period. Plasma concentrations of TA were analyzed using the high performance liquid chromatography with ultraviolet detector, and pharmacokinetic parameters were assigned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
5
10
0
1
Order By: Relevance
“…In this study, the t 1/2ʎz of the tolfenamic acid in geese was 1.73 hr (IV). It was similar to the previous value reported in sheep and goat (1.57-1.94 hr, Corum et al, 2018;Tekeli et al, 2020), but shorter than the value reported in dog, camel, and turtles (5.76-38.92 hr, Jaussaud et al, 1992;Wasfi et al, 1998). Because the t 1/2ʎz is a hybrid parameter consisting Cl T and V d (Toutain & Bousquet-Melou, 2004), the different t 1/2ʎz of tolfenamic acid among species reflects the difference in Cl T and V d .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the t 1/2ʎz of the tolfenamic acid in geese was 1.73 hr (IV). It was similar to the previous value reported in sheep and goat (1.57-1.94 hr, Corum et al, 2018;Tekeli et al, 2020), but shorter than the value reported in dog, camel, and turtles (5.76-38.92 hr, Jaussaud et al, 1992;Wasfi et al, 1998). Because the t 1/2ʎz is a hybrid parameter consisting Cl T and V d (Toutain & Bousquet-Melou, 2004), the different t 1/2ʎz of tolfenamic acid among species reflects the difference in Cl T and V d .…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study that revealed the pharmacokinetics and bioavailability of tolfenamic acid in geese. It has been observed that in livestock, pet animals, and turtles, tolfenamic acid can be used in doses of 2 and 4 mg/kg via various routes of administration (Corum et al, 2018, 2019; CVMP, 1997; Lascelles et al, 2007; Raweewan, Chomcheun, et al, 2020; Raweewan, Laovechprasit, et al, 2020; Tekeli et al, 2020). Therefore, in this study, geese received a habitual dose of 2 mg/kg of tolfenamic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need for studying the pharmacokinetics of tolfenamic acid after extravascular administration in goats, which are the target species. Although the pharmacokinetics of tolfenamic acid in goats have been demonstrated after intravenous (IV; Tekeli et al, 2020) and intramuscular (IM) (Sidhu et al, 2006) administration, no information on pharmacokinetics was found regarding subcutaneous (SC) and oral (PO) routes of administration according to our knowledge. Hence, the aim of this study was to determine the pharmacokinetics and bioavailability of tolfenamic acid (2 mg/kg dose) after IV, IM, SC, and PO administration in goats.…”
Section: Introductionmentioning
confidence: 94%
“…Although the pharmacokinetics of tolfenamic acid in goats have been demonstrated after intravenous (IV; Tekeli et al, 2020) and intramuscular (IM) (Sidhu et al, 2006) administration, no information on pharmacokinetics was found regarding subcutaneous (SC) and oral (PO) routes of administration according to our knowledge.…”
mentioning
confidence: 96%
“…Tolfenamik asitin keçilerde kullanımı Peru, Meksika ve Kosta Rika gibi bazı ülkelerde onaylanmasına karşın Avrupa'da onaylanmamıştır (12). Tolfenamik asitin keçilerde 2 ve 4 mg/kg dozlarda IV ve kas içi (IM) kullanımı önerilmektedir (12,21). Buzağı ve köpeklerde tolfenamik asitin etkisinin doza bağlı olduğu ve doz arttıkça antiinflamatuvar etkisinin artabileceği belirtilmiştir (2,15).…”
Section: Tartişma Ve Sonuçunclassified